Comparison of Zingibinger officinale and Zingibinger zerumbet on antimicrobial activity against enteric bacteria and phytochemical screening / Intan Nabihah Ahmad Fadzil - Ahmad Fadzil, Intan Nabihah (2018)
Both species of the same genus, Zingibinger officinale and Zingibinger zerumbet are known to have biochemical properties such as antioxidants and antibacterial. In this experiment, methanol was used as the solvent. Both type of gingers was powdered and soaked in methanol for 24 hours. The extracts were rotary-evaporated to remove the excess methanol. The extracts of ginger and wild ginger and tested on three species of bacteria which are E.coli, Salmonella spp and Shigella spp by using disc-diffusion method. The positive control used was chloramphenicol with concentration of 30μg and the negative control is the solvent itself which is methanol. When tested with 100 mg/ml of extract concentration, Z. officinale showed slightly visible but weak inhibition zone on Shigella spp and Salmonella spp only. The results are done in triplicate to find and compare means between samples. The p value cannot be from t-test as there were no zone of inhibition for Z. zerumbet extracts thus the standard deviation cannot be calculated. Overall, Z. officinale extracts showed mild effectiveness in inhibiting Salmonella spp and Shigella spp bacteria. Screening of various phytochemicals was also conducted on both extracts of ginger using various reagents. The extracts only differ in presence of condensed tannin and anthocyanin in which only Z. zerumbet has condensed tannin whereas only Z. officinale has anthocyanin.